Serum concentrations of interleukin-6 and tumor necrosis factor alpha in patients with spondyloarthritis: a relationship between systemic inflammation and anemia - К. N. Safarova; E. A. Fedotov; A. P. Rebrov (Бюллетень сибирской медицины, 2022)
Aim. To assess the relationship between the activity of systemic inflammation and the hemoglobin level in patients with spondyloarthritis (SpA).Materials and methods. We examined 92 patients with SpA aged 42.9 ± 11.6 years (SpA duration – 14.8 ± 9.6 years, 55 (60%) men). We calculated the BASDAI and ASDAS-CRP scores, performed complete blood count, evaluated erythrocyte sedimentation rate (ESR), ferrokinetic parameters, C-reactive protein (CRP) level, and serum concentrations of tumor necrosis factor α (TNF-α) and interleukin-6 (IL-6).Results. Anemia was found in 52 (57%) patients: 13 (25%) patients were diagnosed with anemia of inflammation (AI), 39 (75%) individuals had a combination of AI and iron deficiency anemia. A significant increase in CRP (17.8 vs. 9.0 mg / l, respectively; p = 0.001) and ESR (23 vs. 10 mm / h, p < 0.001), a tendency toward an increase in IL-6 levels (5.4 vs. 4.1 pg / ml, p = 0.051), and no difference in TNF-α levels (3.4 vs. 3.0 pg / ml, p = 0.245) were revealed in patients with anemia compared with patients with normal hemoglobin level. The hemoglobin concentration was negatively correlated with the CRP level (r = –0.327, p = 0.001) and ESR (r = –0.527, p < 0.001). IL-6 was positively correlated with the levels of TNF-a, CRP, and ESR (r = 0.431, r = 0.361, r = 0.369; all p < 0.001). With the IL-6 concentration >10 pg / ml, the odds for anemia were 5.3 times higher (95% confidence interval: 1.4–19.9, p = 0.009).Conclusion. The relationship between the activity of systemic inflammation and anemia in patients with SpA was confirmed. Taking into account the pathogenesis of AI, the aim of antianemic treatment is to achieve remission or minimal activity of SpA. Additional studies are required to determine the effect of anti-inflammatory therapy on the development and course of anemia in patients with SpA.